An Insight into the Recent Advancement in Anti-Alzheimer’s Potential of Indole Derivatives and their SAR Study - Mondal, Ritam; Paliwal, Deepika; Thakur, Aman; Kaushik, Niranjan (Current Topics in Medicinal Chemistry, 2025)
Alzheimer is a progressive neurodegenerative disease characterized by change in brain that led to the buildup of specific proteins, ultimately causing brain shrinkage and the death of brain cells. It is the leading cause of dementia, manifesting as a gradual decline in memory, cognitive abilities, behavior, and social functioning, which severely impairs a person’s ability to carry out daily activities. The complexity of Alzheimer’s poses significant challenges to modern medicine, making the development of new therapeutic strategies crucial. Indole derivatives, with their broad spectrum of pharmacological activities, have garnered attention for their potential in treating Alzheimer’s disease. This review provides a detailed summary of recent progress in developing indole derivatives as therapeutic agents for Alzheimer's disease. It thoroughly examines the pharmacological properties of various indole derivatives, including their mechanisms of action. These compounds have been shown to influence several processes, such as amyloid-beta aggregation, MAO inhibition, AChE and BuChE inhibition. Furthermore, this review discusses the structural modifications of indole derivatives designed to improve their therapeutic effectiveness.
Keywords: mono-amine oxidase